High genetic variation in resting‐stage production in a metapopulation: Is there evidence for local adaptation?. (29th September 2015) - Roulin, Anne C.; Mariadassou, Mahendra; Hall, Matthew D.; Walser, Jean‐Claude; Haag, Christoph; Ebert, Dieter
<x xml:space="preserve">Abstract</x> Local adaptation is a key process for the maintenance of genetic diversity and population diversification. A better understanding of the mechanisms that allow (or prevent) local adaptation constitutes a key in apprehending how and at what spatial scale it occurs. The production of resting stages is found in many taxa and reflects an adaptation to outlast adverse environmental conditions. Daphnia magna (Crustacea) can alternate between asexual and sexual reproduction, the latter being linked to dormancy, as resting stages can only be produced sexually. In this species, on a continental scale, resting‐stage production is locally adapted—that is, it is induced when the photoperiod indicates the imminence of habitat deterioration. Here, we aimed to explore whether selection is strong enough to maintain local adaptation at a scale of a few kilometers. We assessed life‐history traits of 64 D. magna clones originating from 11 populations of a metapopulation with permanent and intermittent pool habitats. We found large within‐ and between‐population variation for all dormancy‐related traits, but no evidence for the hypothesized higher resting‐stage production in animals from intermittent habitats. We discuss how gene flow, founder events, or other forms of selection might interfere with the process of local adaptation.